Komunikasi dakwah efektif Badiuzzaman Said Nursi: kajian terhadap latar belakang Turki penghujung abad ke-19 masihi / Muaz Mohd Noor, S. Salahudin Suyurno dan Faridah Mohd Sairi - Mohd Noor, Muaz; Suyurno, S. Salahudin; Mohd Sairi, Faridah (Academy of Contemporary Islamic Studies (ACIS), 2021)
Eminent Scholar of Islam, Imam Bediüzzaman Said Nursi was born in 1877 AD (1298 AH) in Bitlis, eastern Turkey. As well as his strong memory and intelligence, he was known with his purity, taqwa (avoidance of sins), and courage. This article is a review on the methodology of da'wah of Said Nursi in The Words, one of the Rasail al-Nur Collection. Since the problem very diverse and complex nature of the various ethnic groups, especially the variety, the preachers of today need to be able to play multiple roles in a homogenous society. This study attempts to study the history and background of Turkey during the time of Said Nursi (at the end of 19th century). What is the factor that causes him to be so committed in the field of da'wah, until he has mastered in the methods and skill of good communication during da'wah, whether verbal and non-verbal communication. He never hesitated to declare the right way (amr bil ma'ruf) and condemn the wrong way (nahy anil munkar) against unjust leaders and governors of the time, but in a wise way. The methodology of this study uses qualitative methods to achieve the objectives of the study using data collection through library research and SLR (Systematic Literature Review). The results of the study found that the mastery of solid communication knowledge and extensive experience of preaching to the community field caused a successful dakwah effort.